2013
DOI: 10.5352/jls.2013.23.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Food Processing Methods for Larvae of Allomyrina dichotoma, Korean Horn Beetle

Abstract: With the objective of developing a functional food source, we established optimal processing conditions for the larvae of Allomyrina dichotoma, which have been used in traditional medicine to treat hepatic disorders in Korea. Without suitable processing, the larvae are difficult to consume as a food because of their disgusting taste and smell; moreover, in this form they might be a potential microbial hazard. In this study, we investigated the effect of feeding material, sterilization, and powdering after free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…There has been an interest in developing effective bioactive products using beetles for health supplements or functional foods because of their nutrient components such as unsaturated fatty acids, proteins, vitamins, fiber, and minerals [11,32,33]. Recently, it was reported that Protaetia brevitarsis larvae (PBL) or Allomyrinal dichotoma larvae (ADL) have antioxidant, hepatoprotective, anti-neoplastic, and antiobesity properties [11,20,22,34].…”
Section: Discussionmentioning
confidence: 99%
“…There has been an interest in developing effective bioactive products using beetles for health supplements or functional foods because of their nutrient components such as unsaturated fatty acids, proteins, vitamins, fiber, and minerals [11,32,33]. Recently, it was reported that Protaetia brevitarsis larvae (PBL) or Allomyrinal dichotoma larvae (ADL) have antioxidant, hepatoprotective, anti-neoplastic, and antiobesity properties [11,20,22,34].…”
Section: Discussionmentioning
confidence: 99%
“…부식토나 부후목에 서식하며 교육 및 애완용으로도 널리 사 육하고 있으며 다른 곤충들에 비해서 생태 및 생활사가 비교적 잘 알려져 있는 곤충이다 (Kim and Kang, 2005). 최근에는 장수 풍뎅이 유충이 성인병 치료 및 예방에도 효능을 지닌다고 하여, 한약재료나 식품소재로 활용하려는 연구가 시도되고 있다 (Chung et al, 2013 (Stach et al, 2003;Schäfer et al, 2010). 냉동 (-80℃) 호열성 균주로 보고되었다 (Wang et al, 1996;Kim et al, 1999;Goodfellow et al, 2005;Puhl et al, 2009), 그 외에 clone S04 와 유사한 Saccharopolyspora hordei DSM 44065 T 는 60℃, clone S11과 유사한 Microbispora hainanensis 211020 T 는 50℃ 까지 생육이 가능한 것으로 보고되었다 (Goodfellow et al, 1989;Xu et al, 2012).…”
Section: 장수풍뎅이 유충 방선균의 다양성 및 항균활성 157unclassified
“…Insects are a highly nutritious and healthy food source rich in unsaturated fatty acid, proteins, vitamins, fiber, and minerals (Huis et al 2013;Yoo et al 2013;Chung et al 2013a), suggesting that insects can be used as health supplements or functional foods (Ahn et al 2000(Ahn et al , 2002Nam & Ma 2000;Park 2001). Korean horn beetle (A. dichotoma) larvae have been used for treatment of various liver diseases, and recently have been investigated as a potential human food product in Korea (Chung et al 2013b). Korean horn beetle (A. dichotoma) larvae have been used for treatment of various liver diseases, and recently have been investigated as a potential human food product in Korea (Chung et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that cricket extracts could be used as anti-obesity agents to reduce high fat content in blood (Hwang et al 2004). Korean horn beetle (A. dichotoma) larvae have been used for treatment of various liver diseases, and recently have been investigated as a potential human food product in Korea (Chung et al 2013b). However, the effect of A. dichotoma larvae on obesity or metabolic diseases has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%